1988
DOI: 10.1148/radiology.167.1.2831562
|View full text |Cite
|
Sign up to set email alerts
|

Muscle necrosis in the extremities: evaluation with Tc-99m pyrophosphate scanning--a retrospective review.

Abstract: A retrospective review was done of 34 extremities studied between 1981 and 1985 with technetium-99m pyrophosphate scanning; 22 were subsequently amputated. Results of detailed pathologic examination or immediate postoperative examination of the resected extremity were available in 16 cases. In these cases, scanning had allowed correct prediction of the level of amputation and of the specific areas of muscle infarction in 13 cases. In the one case in which amputation was performed for infection rather than musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…A number of tracers, particularly 99m Tc-labeled phosphonates and 99m Tc pyrophosphate (PYP), accumulate in damaged soft tissue [37][38][39]. The degree of tracer accumulation is often a good index of the extent of tissue damage [40][41][42].…”
Section: Radiotracer Imaging Of Electrical Injurymentioning
confidence: 99%
“…A number of tracers, particularly 99m Tc-labeled phosphonates and 99m Tc pyrophosphate (PYP), accumulate in damaged soft tissue [37][38][39]. The degree of tracer accumulation is often a good index of the extent of tissue damage [40][41][42].…”
Section: Radiotracer Imaging Of Electrical Injurymentioning
confidence: 99%
“…The tracer is distributed across both plasma and mitochondrial membranes in response to progressively larger negative transmembrane potentials, and trapped within the mitochondrial layer [32]. In a study by Timmons et al, 99mTc pyrophosphate scintigraphy allowed accurate prediction of the location of necrotic muscle [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the remaining patient ( patient 1), who showed nonperfused and non-viable areas of edematous muscle in the entire brachialis muscle, we believe that the brachialis muscle damage may be more closely related to direct electrical injury than to progressive ischemic necrosis of the muscle because conventional angiography of the upper Tc-99m pyrophosphate (PYP) scanning is a useful modality to visualize the site and extent of damaged muscles (2, 3). Timmons et al (2) reported on their experience with using Tc-99m PyP scanning for evaluating the muscle necrosis of 16 patients. In that study, they found a sensitivity of 87%, with complete anatomic agreement in 81% of the cases.…”
Section: Discussionmentioning
confidence: 99%
“…A high-voltage electrical burn has extensive soft tissue injury beneath a relative small skin wound of the contact point, and a high-voltage electrical burn is often associated with deep muscle injuries. Hidden, undetected deep muscle injuries have a tendency for progressive tissue necrosis, and this can lead to major amputations or sepsis (2,3). Thus, it is important to identify the site and extent of non-viable deep muscle damage for performing proper debridement so as to avoid further tissue injury in these patients.…”
mentioning
confidence: 99%